Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. (June 2023) - Ding, Kang; Wu, Zi-Yao; Zhang, Nuan; He, Jun; Zhang, Fan; Wu, Jing-Jing; Bai, Hong-Jin; Zhang, Wei-Ku; Li, Lin; Xu, Jie-Kun
Abstract: Six undescribed macrocyclic daphnane orthoesters, stelleratenoids A−F (1 −6 ), were isolated from the roots of Stellera chamaejasme L. Their structures were elucidated by extensive spectroscopic analyses, including HRESIMS and NMR spectra. Compound 1 features an unusual terminal double bond at C-2/C-19 in the 1 α -alkyldaphnane lactone skeleton. Compounds 2 −4 are unique in the presence of different long chain fatty acyl groups. Compounds 5 and 6 are unique examples of modified macrocyclic daphnane diterpenoids. All the isolates were evaluated for anti-HIV activity in MT-2 cells. Among them, compounds 1, 5 and 6 exhibited highly potent anti-HIV activity with EC50 values of 66.70, 10.62 and 55.10 nM, respectively, possessing high potential to develop new anti-HIV drugs. Graphical abstract: Six undescribed macrocyclic daphnane orthoesters, stelleratenoids A−F (1−6 ), were obtained from the roots of Stellera chamaejasme L. Compounds 1, 5 and 6 exhibited significant anti-HIV activity at nanomolar concentrations. Image 1 Highlights: Six undescribed macrocyclic daphnane orthoesters, stelleratenoids A−F (1 −6 ), were isolated from Stellera chamaejasme L. Compound 1 possesses an unusual C-2/C-19 terminal double bond in the 1 α -alkyldaphnane lactone skeleton. Compounds 1, 5 and 6 exhibited highly potent anti-HIV activity with EC50 values of 66.70, 10.62 and 55.10 nM, respectively.